Global Navigation Satellite System (GNSS) radio occultation climatologies mapped by machine learning and Bayesian interpolation - E. Shehaj; E. Shehaj; S. Leroy; K. Cahoy; A. Geiger; L. Crocetti; G. Moeller; G. Moeller; B. Soja; M. Rothacher (Atmospheric Measurement Techniques)
Global Navigation Satellite System (GNSS) radio occultation (RO) is a space-based remote sensing technique that measures the bending angle of GNSS signals as they traverse the Earth's atmosphere. Profiles of the microwave index of refraction can be calculated from the bending angles. High accuracy, long-term stability, and all-weather capability make this technique attractive to meteorologists and climatologists. Meteorologists routinely assimilate RO observations into numerical weather models. RO-based climatologies, however, are complicated to construct as their sampling densities are highly non-uniform and too sparse to resolve synoptic variability in the atmosphere.